Temporomandibular joint internal derangement in mandibular asymmetry. What is the relationship? - Buranastidporn B. (2014)
The purpose of this study was to clarify the contributing factors and their influences on temporomandibular joint internal derangement (TMJ ID) symptoms in subjects with mandibular asymmetry. Postero-anterior (PA) cephalograms of 187 pre-orthodontic treatment subjects (aged 18-45 years, mean 23.9 years) were used to investigate the inclination of the frontal occlusal (FOP) and frontal mandibular (FMP) planes to determine vertical asymmetry. Mandibular dental midline shift (DMS) and mandibular midline shift (MMS) were studied to determine transverse asymmetry. The degree of asymmetry was analysed in conjunction with the results from self-administered TMJ ID history forms. A prevalence of TMJ ID was most related to the inclination of the FMP (P < 0.01), with the symptoms being notably higher when the cant was greater than 3 degrees. The symptomatic side was related only to the inclination of the FOP and FMP. Symptoms confined to the ipsilateral side were primarily found in subjects with mild asymmetry, whereas symptoms on both sides and those on the contralateral side were greater in those with moderate and severe asymmetry, respectively. No significant correlation was found for DMS and MMS. The results suggest that the degree of asymmetry in the vertical dimension is significantly correlated with TMJ ID symptoms.